Affective Dynamics in Youth Problematic Internet Use Heterogeneous Trajectories: Longitudinal Cross‐Lagged Network Analysis of Anxiety, Depression, and Stress. - Qi, Huaiyuan; Shi, Hongqiao; Li, Jiangyong; Li, Meng; Chen, Xuhuai; Luo, Yangmei (Stress & Health: Journal of the International Society for the Investigation of Stress, 2026)
A growing body of research links problematic internet use (PIU) in youth to anxiety, depression, and stress, yet the dynamic interactions between these negative emotions, heterogeneous PIU trajectories, and their dimensional drivers remain unclear. To address this gap, a two‐wave longitudinal study of 5108 Chinese students (Mage = 18.28, SD = 0.84; 67.6% female) identified distinct PIU trajectories based on empirical longitudinal data and used cross‐sectional/cross‐lagged network analyses to explore these dynamics. Cross‐sectional findings showed that the Remitted group had lower negative emotion levels and inter‐network connection strength over time, whereas the Incident group exhibited the reverse; specific anxiety symptoms (e.g., "restlessness" in Incident PIU) also had the strongest links to overall emotional network cohesion. Cross‐lagged analyses further indicated that in the Persistent/Incident groups, stress symptoms acted as the primary trigger for subsequent negative emotions. Moreover, their cross‐lagged emotional networks had significantly higher global strength than those of the Remitted/Persistent Non‐PIU groups. These findings suggest that emotional network features vary by PIU trajectory group and that stress symptoms may be the core driver of emotional deterioration in the Persistent/Incident groups. The study emphasises intervention priorities: prioritise stress management for Persistent/Incident groups to prevent emotional deterioration, and monitor residual emotional connections in Remitted groups to avoid recurrence.